Converging cultures of communication: A comparative study of Internet use in China, Europe, and the United States. (July 2021) - Ørmen, Jacob; Helles, Rasmus; Bruhn Jensen, Klaus
Global Internet use is circumscribed by local political and economic institutions and inscribed in distinctive cultural practices. This article presents a comparative study of Internet use in China, the United States, and five European countries. The empirical findings suggest a convergence of cultures, specifically regarding interpersonal communication, alongside characteristic national and sociodemographic configurations of different prototypes of human communication. Drawing on the classic understanding of communication as a cultural process producing, maintaining, repairing, and transforming a shared reality, we interpret such configurations as cultures of communication, which can be seen to differ, overlap, and converge across regions in distinctive ways. Looking beyond traditional media systems, we call for further cross-cultural research on the Internet as a generic communication system joining global and local forms of interaction.